Sensorized Foam Actuator with Intrinsic Proprioception and Tunable Stiffness Behavior for Soft Robots. (18th May 2021) - Murali Babu, Saravana Prashanth; Visentin, Francesco; Sadeghi, Ali; Mondini, Alessio; Meder, Fabian; Mazzolai, Barbara
Abstract : Soft robots require actuators with integrated sensing components that perceive unstructured, dynamic environments without compromising their performance. However, many soft robotic systems still rely on external sensors, which affect the functionality, response time, and payload. To overcome these issues, herein a sensorized foam actuator (SFA) with a foam core that acts as both an actuator and a proprioception‐sensing element is developed. The integrated modules can sense direct actuation and passive deformation due to extrinsic stresses through a specific pore shape evolution, which leads to a distinct variation in the resistivity pattern. In addition, a fiber‐reinforced skin encapsulating the SFA facilitates a fast and efficient response. The SFA is able to lift more than 500 times its own weight with a load‐withstanding capacity of 235 N, linear contraction up to 70% strain, and a recovery speed of 13.3 mm s −1 . In addition, the SFA is lightweight (34 g), has low hysteresis (<4%), and can self‐sense its current deformation state. As proof of concept, various soft robotic applications are presented such as compression piston‐like motion, modular inchworm‐like crawling locomotion, and a robotic trunk‐like manipulation. Abstract : Herein, a smart integrated design combining a sensor and actuation into a single component is introduced. The variable actuation modes ensure that the stiffness can be tuned and that the actuator responds rapidly. The proprioceptive and stiffness behavior of the actuator facilitates a strong yet soft and robust actuator.